Arnold's Missed Rhymes. Issue 2 (July 2017) - Perry, Seamus
Abstract : Matthew Arnold's poetry has often been criticised for its technical ineptitude, including the inadequacy of its rhymes. This essay argues that Arnold was particularly attuned to the scope and possibility of rhyme, and (by extension) misrhyme, and that his practice demonstrates this awareness; and, using a range of examples from across his works, the essays seeks to show the ways in which misrhyme and missing rhyme contribute to the distinctive atmosphere of his verse.